2019
DOI: 10.1175/jcli-d-18-0577.1
|View full text |Cite
|
Sign up to set email alerts
|

Interannual Variability of the North Pacific Mixed Layer Associated with the Spring Tibetan Plateau Thermal Forcing

Abstract: By using multisourced data and two sets of sensitivity runs from the coupled general circulation model CESM1.2.0, we investigated the effects of the spring [March, April, and May (MAM)] surface sensible heating over the Tibetan Plateau (SHTP) on the interannual variability of the North Pacific Ocean sea surface temperature (SST) and mixed layer. The results indicated that an above-normal MAM SHTP can generate a Rossby wave downstream and form an anomalous equivalent barotropic anticyclone over the North Pacifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 70 publications
3
35
0
Order By: Relevance
“…Sun et al . [ 122 ] also indicated that TP SH in spring could affect the North Pacific by generating an anomalous barotropic atmospheric circulation. As a result, the underlying SST is altered significantly through sea surface heat exchange and Ekman transport (Fig.…”
Section: Tp and Oceans: Synergistic Climate Influencementioning
confidence: 99%
“…Sun et al . [ 122 ] also indicated that TP SH in spring could affect the North Pacific by generating an anomalous barotropic atmospheric circulation. As a result, the underlying SST is altered significantly through sea surface heat exchange and Ekman transport (Fig.…”
Section: Tp and Oceans: Synergistic Climate Influencementioning
confidence: 99%
“…All these datasets cover the time period 1980-2014. A 2-9 years bandpass Lanczos filter was applied to these datasets after the linear trends had been removed to extract the signals of interannual variability (Sun et al 2019).…”
Section: Datamentioning
confidence: 99%
“…2b). Similar experimental designs were adopted in Sun et al (2019) and Zhao et al (2021). Each sensitivity experiment contained 15 members provided by 15 different initial conditions from CTRL to remove the interference by atmospheric noise, and each member was integrated from May 1st to August 1st.…”
Section: Modelmentioning
confidence: 99%